Correlation Between Age with Cholesterol Levels, Random Blood Sugar (GDS) and Uric Acid - Sabilu, Yusuf; Irma, Irma (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Age is one of the important variables in the incidence of degenerative diseases such as heart disease, stroke, diabetes mellitus (DM), and kidney disorders. It is estimated that by 2030, there will be an increase in deaths due to degenerative diseases in the world, namely ischemic heart disease of around 7.2 million cases and stroke of around 5.5 million cases. This is a double burden in various countries, including Indonesia. This analytical observational study with a cross-sectional design aims to analyze the correlation between age factors and cholesterol levels, time blood sugar levels (TBS), and uric acid levels. The sample involved in this study was 24 people who were taken using the purposive sampling technique. Analysis of the data for the correlation test uses the Spearman test. The results showed that the increase in cholesterol levels (P value = 0.000 < = 0.05 with R = 0.703), TBS levels (P value= 0.454 > =0.05 with R=0.160), and uric acid levels (P value= 0.454 > =0.05 with R=0.235). It can be concluded that age positively correlates with cholesterol levels, meaning that the older a person is, the higher their cholesterol levels. Age does not correlate with GDS levels and uric acid levels. It is expected that the higher-age person must change his lifestyle to a healthy lifestyle to avoid various disease problems, especially degenerative diseases that are closely related to lifestyle.